Integration of Industrial and Surgical Robotic Systems: A Case Study of Combining the SCARA Robot with the Da Vinci Robot - Kadid, Lara Fathi; Kazzaz, Hasan Khaled; Issa, Mohamad Adib (Journal of engineering sciences and information technology, 2025)
Objectives:  The field of robotics is rapidly evolving toward more precise, flexible, and cost-effective solutions in industrial and medical environments. This study explores the potential of integrating a Selective Compliance Assembly Robot Arm (SCARA) (Revolute-Prismatic-Revolute-Revolute) (RPRR), known for its high speed and precision in repetitive horizontal and vertical movements used in industrial or assistive tasks such as handling instruments, with the da Vinci surgical robot, which is characterized by its high-precision control and ability to perform precise and complex movements in surgical procedures. This integration aims to design a hybrid system that leverages the characteristics and advantages of both industrial and surgical robots, with the goal of opening new horizons in precision automation, particularly in the fields of biomanufacturing and complex surgical procedures. It seeks to leverage the characteristics of each robot to enhance work efficiency, reduce operating time, and increase the level of precision, safety, and adaptability to advanced, highly sensitive environments. Methods:  This study builds a prototype demonstrating the communication and mutual control mechanism between the SCARA robot, which is characterized by its precision and speed in horizontal and vertical movements, and the surgical tools of the da Vinci robot, which perform complex and precise surgical movements inside the patient's body. The main goal of the proposed robot is to combine the performance stability of industrial robots with the flexibility and precision of surgical robots, paving the way for the development of low-cost robots that combine the advantages of industrial and surgical robots to perform surgeries with high efficiency. Results: The SolidWorks simulation environment was used to analyze the motion of the robotic arm proposed in this research. The motion transmission mechanism was studied through the torque required to move the joint and the joint's angular motion. Experimental results demonstrated a 20-fold increase in torque at the third joint (9600 N.mm compared to the required torque of 8550 N.mm), with arm movement from 0° to 90° in approximately 2.2 seconds. and a 123% factor of safety (F O S) was achieved for the second joint.
Keywords: da Vinci robot; Hybrid robot; Industrial robots; SCARA robot; Surgical robots